In situ time resolved wide angle X-ray diffraction study of nanotube carpet growth: Nature of catalyst particles and progressive nanotube alignment. (June 2015) - Landois, Périne; Pinault, Mathieu; Rouzière, Stéphan; Porterat, Dominique; Mocuta, Cristian; Elkaim, Erik; Mayne-L'Hermite, Martine; Launois, Pascale
Abstract: Catalytic chemical vapor deposition is the most promising process to obtain vertically aligned carbon nanotube (VACNT) carpets. Live analysis of growing VACNT is crucial to reveal their nucleation and growth mechanisms. We present novel time resolved in situ X-ray diffraction (XRD) analysis on growing macroscopic VACNT carpets enabling us to get statistical information on catalytic phase together with nanotube progressive alignment. A specific synthesis set-up has been developed to perform such in situ synchrotron XRD experiments. Nucleation kinetics of the different phases are evidenced: first, orthorhombic Fe3 C crystalline phase is formed, followed by the formation of CNTs and finally of γ-Fe, demonstrating that Fe3 C particles are the nucleation seeds for CNT growth. The additional formation of Fe3 C or γ-Fe nanowires inside CNTs is associated with capillary forces and mobility of them at 850 °C. Experiments also reveal the progressive formation and alignment of VACNT carpets during the continuous precursor injection. Quantification of the alignment degree allows one to get a better understanding of the effect of precursor injection rate and CNT length on VACNT alignment. The overall results are key issues for the scaling-up of VACNT synthesis and their applications towards commercialization.